2017
DOI: 10.1093/jee/tow292
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Prevalence ofRaffaelea lauricola, Cause of Laurel Wilt, in Different Species of Ambrosia Beetle in Florida, USA

Abstract: We summarize the information available on ambrosia beetle species that have been associated in Florida with Raffaelea lauricola T.C. Harr., Fraedrich & Aghayeva, the primary symbiont of Xyleborus glabratus Eichhoff and cause of laurel wilt. In total, 14 species in Ambrosiodmus, Euwallacea, Premnobius, Xyleborus, Xyleborinus, and Xylosandrus were either reared from laurel wilt-affected host trees or trapped in laurel wilt-affected stands of the same, and assayed for R. lauricola. In six collections from native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 36 publications
1
50
1
1
Order By: Relevance
“…On the other hand, Raffaelea species were not detected in this study, although this genus is frequently reported in ambrosia interactions (Ceriani-Nakamurakare et al 2016;Ploetz et al 2017). These results could be due to the known problems of using ITS markers with certain groups of ambrosial fungi (Fraedrich et al 2008;Kostovcik et al 2015).…”
Section: Discussioncontrasting
confidence: 61%
“…On the other hand, Raffaelea species were not detected in this study, although this genus is frequently reported in ambrosia interactions (Ceriani-Nakamurakare et al 2016;Ploetz et al 2017). These results could be due to the known problems of using ITS markers with certain groups of ambrosial fungi (Fraedrich et al 2008;Kostovcik et al 2015).…”
Section: Discussioncontrasting
confidence: 61%
“…that are native to the southeastern United States, but only 6% (58 of 931) of those that were associated with avocado. Raffaelea lauricola was recovered from 10 of the ambrosia beetle species that were assayed, including X. glabratus, but was most prevalent in Xyleborus congeners [70]. Previous reports had suggested that Raffaelea spp.…”
Section: Vectors Of Raffaelea Lauricolamentioning
confidence: 99%
“…Several other species are associated with redbay, avocado and other lauraceous hosts, but they have been considered as vectors of R. lauricola only recently. The general absence of X. glabratus in avocado orchards that are affected by laurel wilt, the pathogen's presence in other species of ambrosia beetle that are recovered from avocado and other host trees, and the experimental demonstration of pathogen transmission and subsequent laurel wilt development in redbay and avocado suggest that species other than X. glabratus could play roles in the epidemiology of this disease [1,69,70].…”
Section: Ambrosial Symbiosesmentioning
confidence: 99%
See 2 more Smart Citations